Bayesian approach to forecasting in small firms - Paul L. Reynolds; Alexander Ivanovich Kovalyov (Вестник СибАДИ, 2017)
The authors, represented the University of Huddersfield in United Kingdom and Omsk financial university in Russia, investigate the problems of forecasting in small firms. On the basis of studying activity of Russian and English forms there are educed the barriers on the way of effective realization of a such important function of management as forecasting. It is proved that for small frims the Bayesian approach is the most acceptable for forecasting, the distinctive peculiarity of which is using, on the way with objective, subjective information, which may be obtained and systematized on the basis of subjective judgements of entrepreneurs who have a small business. As a practice shows, exactly subjective judgements play the significant role in making managerial decisions in small business.